Tekanan Darah Pada Atlet - Al Ghifari, Ghaza Ahmad; Berawi, Khairun Nisa; Graharti, Risti; Kurniati, Intanri (Medula, 2025)
Blood pressure in athletes is an important topic in exercise physiology studies, given its influence on performance and long-term health. In general, athletes exhibit lower blood pressure at rest compared to sedentary individuals, as a result of the body's adaptation to regular physical exercise. The purpose of this method is to analyze and collate knowledge relevant to the research topic. In this study, 12 articles from national and international journals published between 2015 and 2023 were used. The articles were obtained from databases such as PubMed and Google Scholar. The collected sources were then analyzed using the systematic literature review method. The result of this study is that blood pressure in athletes can be different compared to individuals who are not involved in intense physical activity, due to the body's adaptation to regular exercise. Blood pressure in athletes is influenced by a variety of factors, including sport type, training pattern, age, gender, as well as genetic and environmental factors. Understanding these blood pressure patterns is important for optimizing performance and maintaining cardiovascular health in athletes.